Peran Literasi dan Inklusi Keuangan Syariah dalam Meningkatkan Kinerja UMKM di Kabupaten Kuningan - Rifqi Muthoharul Janan; Abdul Rosyid; Ayus Ahmad Yusuf; Dewi fatmasari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the role of Islamic financial literacy and Islamic financial inclusion in improving the performance of Micro, Small, and Medium Enterprises (MSMEs) in Kuningan Regency. The research employs a descriptive qualitative approach, focusing on the understanding, experiences, and practices of MSME actors in accessing and utilizing Islamic financial services. Data were collected through in-depth interviews, observations, and documentation involving MSME actors, Islamic financial institutions, and related stakeholders. The findings indicate that Islamic financial literacy plays a crucial role in shaping MSME actors’ understanding of Sharia-based transaction principles, thereby encouraging business decision-making that aligns more closely with values of justice and sustainability. Islamic financial inclusion also makes a tangible contribution through easier access to financing, savings products, and other Islamic financial services that support improved business performance. Nevertheless, several challenges remain, including limited understanding, insufficient socialization, and unequal access to Islamic financial services. This study concludes that strengthening Islamic financial literacy and expanding Islamic financial inclusion are strategic factors in enhancing MSME performance in Kuningan Regency. Therefore, synergy among local governments, Islamic financial institutions, and MSME actors is required to promote the development of competitive MSMEs grounded in Sharia principles.